2017
DOI: 10.2147/ijn.s125300
|View full text |Cite
|
Sign up to set email alerts
|

Convection enhanced delivery of panobinostat (LBH589)-loaded pluronic nano-micelles prolongs survival in the F98 rat glioma model

Abstract: Background The pan-histone deacetylase inhibitor panobinostat is a potential therapy for malignant glioma, but it is water insoluble and does not cross the blood–brain barrier when administered systemically. In this article, we describe the in vitro and in vivo efficacy of a novel water-soluble nano-micellar formulation of panobinostat designed for administration by convection enhanced delivery (CED). Materials and methods The in vitro efficacy of panobinostat-loaded na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…One method to overcome this limitation is to package the drug in a water-soluble nanoparticle or micelle. 26 The translation of this nanoparticle formulation of panobinostat to the clinic is challenging, as the breakdown and metabolism of the encapsulating nanoparticle within the brain is unknown, as is its potential for long-term accumulation or toxicity. An alternative method of producing a water-soluble formulation of panobinostat designed for CED may allow a quicker path to the clinic.…”
mentioning
confidence: 99%
“…One method to overcome this limitation is to package the drug in a water-soluble nanoparticle or micelle. 26 The translation of this nanoparticle formulation of panobinostat to the clinic is challenging, as the breakdown and metabolism of the encapsulating nanoparticle within the brain is unknown, as is its potential for long-term accumulation or toxicity. An alternative method of producing a water-soluble formulation of panobinostat designed for CED may allow a quicker path to the clinic.…”
mentioning
confidence: 99%
“…Panobinostat, among other drugs, is being currently considered for early stage clinical trials facilitating drug delivery by convection-enhanced delivery-a catheterbased method in which the study agent is directly infused into the target tissue. 74,75 Another HDAC inhibitor that has been studied in the context of HGGs is vorinostat (SAHA); early studies in children with HGGs demonstrated good tolerability and have now moved to phase II studies in combination with radiation and TMZ 76 (ClinicalTrials.gov NCT01189266). A combination of vorinostat and the mTor inhibitor temsirolimus (NCT02420613) is also currently ongoing.…”
Section: Targeted Therapeutic Approachesmentioning
confidence: 99%
“…CED of nanodiamonds complexed with doxorubicin enhanced tissue retention, localized its toxicity and provided prolonged survival in rats with intracranial tumors [27]. Nano-micelles loaded with panobinostat, a strongly hydrophobic drug that is unstable when delivered in its unmodified form, prolonged survival of tumor-bearing rats [28]. Lipidoid nanoparticles encapsulating truncated diphtheria toxin were delivered by CED and inhibited brain tumor growth [29].…”
Section: Nanocarriers Encapsulating Therapeutic Agentsmentioning
confidence: 99%
“…These include EGFR inhibitors (cetuximab, erlotinib, gefitinib), PI3K/mTOR inhibitors (everolimus, tacrolimus, sirolimus), pan-histone deacetylase inhibitor (panobinostat), and monoclonal antibodies such as those against VEGF (bevacizumab) [82]. Panobinostat, a strongly hydrophobic drug with poor BBB permeability, has been shown to be much more effective when loaded into nano-micelles [28]. Nanoencapsulation and local delivery of these agents could dramatically improve their activity against GBM tumors.…”
Section: Novel Therapeutic Agents For Treatment Of Brain Tumorsmentioning
confidence: 99%